Consumers’ awareness towards organic rice in Malaysia - Ibitoye, O. O.; Mohd Nawi, Nolila; Kamarulzaman, Nitty Hirawaty; Man, Norsida (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
Not many attempts have been made in previous studies to understand consumers’ sociodemographic characteristics and their awareness towards organic rice. Knowledge towards organic rice among consumers is fundamental to induce demand and market for organic rice. This study seeks to understand consumers’ awareness towards organic rice in Malaysia. The survey is exploratory in nature and was conducted at major supermarkets in Klang Valley. Data were analysed using descriptive analysis and chi-square analysis using cross-classification techniques, and correlation to determine their relationship, strength and direction of their relationship. The findings showed majority of the respondents (85.6%) have some level of awareness towards organic rice, while only 64.7% planned to consume organic rice in the future. This indicates that awareness of consumers towards organic rice does not necessarily translate to their planning to consume organic rice. Thus, achieving awareness and understanding the linkage between awareness and consumption is fundamental to impacting demand and market for organic rice. The study also showed that the younger respondents have more concern towards organic rice. These findings if well responded to, would definitely have positive implications for the Malaysian organic rice industry.